A novel method combining strata movement and UAV infrared remote sensing technology to evaluate mining ground damage - Yixin Zhao; Kangning Zhang; Chunwei Ling; Jihong Guo; Bo Sun (International Journal of Coal Science & Technology)
Abstract Mining-induced ground fissures are common problems associated with mining damage in shallowly buried coal seams in the western mining area of China. To evaluate the surface mining damage of the 12203 working face of the Huojitu Colliery in Shendong mining area, low-altitude infrared aerial surveys were conducted on the ground at the static fissure area (O-A1) and the dynamic fissure area (O-A2) of the working face. The temperature evolution patterns of fissures, sand and plants in the infrared images were analysed. The relationship between overburden fractures and surface fissure temperature was revealed, and the influence range and temperature self-healing period of the surface affected by underground mining were determined. The results indicated that underground mining could lead to a decrease in the ground temperature above the working face. The surface temperature evolution can be divided into three zones: a temperature stabilization zone before mining, a temperature cooling zone during mining, and a temperature recovery zone after mining. The temperature of sand and plants above the working face exhibited quadratic curve changes in O-A1 and O-A2, respectively. The length of the temperature reduction zone affected by mining is 40 m in O-A2, and 46.8 m in O-A1. The temperature recovery periods of ground fissures in O-A1 and O-A2 were 4.0 and 4.6 d, respectively. These findings could provide a basis for evaluating mining ground damage.